Managerial Economics and Global Competition - Silvio M. Brondoni (Symphonya, 2005)
Global managerial economics tends to emerge in conditions of strong, continuous competitive tension, in contexts that are open and subject to political, social and technological instability. Globalisation and new competition boundaries oblige companies to adopt a new ‘market-oriented competitive management philosophy’ (market-driven management), in which customer value management predominates. Global managerial economics thus interfaces with numerous competition spaces, all with different levels of competitive intensity, and market-driven corporate management thus refers to specific competitive conditions, which may typically be summed up as: conditions of scarcity of supply (D>S), with business economics focused on price competition; conditions of controlled competition (D~S), where management economics embodies widespread internationalisation and non-price competition policies; conditions of over-supply (D<S), where management economics underlines the central role of corporate and product intangible assets.